NMR Data Interpretation Explained : Understanding 1D and 2D NMR Spectra of Organic Compounds and Natural Products - Neil E. Jacobsen (Wiley, 2017)
NMR Data Interpretation Explained shows how to get from an NMR spectrum to a chemical structure through numerous examples and exercises. Each topic is introduced with one or more examples of NMR data accompanied by detailed explanations of the interpretation of that data. Examples are then followed by a number of exercises using detailed images of NMR data. These are followed up by solutions, again with detailed explanations of the step-by-step reasoning used to solve the exercises